(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
In this paper, we formulate a two-way interfacial condition for simulating lattice dynamics in one space dimension. With a time history treatment, the incoming waves are incorporated into the motion of the boundary atoms accurately. This condition reduces to the absorbing boundary condition when there is no incoming wave. Numerical tests validate the effectiveness of the proposed condition in treating simultaneously incoming waves and outgoing waves.